Relative Entropy and Optimization-Driven Coarse-Graining Methods in VOTCA. - S Y Mashayak; Mara N Jochum; Konstantin Koschke; N R Aluru; Victor Rühle; Christoph Junghans (PLoS ONE, 2015)
We discuss recent advances of the VOTCA package for systematic coarse-graining. Two methods have been implemented, namely the downhill simplex optimization and the relative entropy minimization. We illustrate the new methods by coarse-graining SPC/E bulk water and more complex water-methanol mixture systems. The CG potentials obtained from both methods are then evaluated by comparing the pair distributions from the coarse-grained to the reference atomistic simulations. In addition to the newly implemented methods, we have also added a parallel analysis framework to improve the computational efficiency of the coarse-graining process.